Regional Splanchnic Oxygenation during Continuous versus Bolus Feeding among Stable Preterm Infants - Gisela Laura Sirota; Ita Litmanovitz; Carmel Vider; Shmuel Arnon; Shiran Sara Moore; Eynit Grinblatt; Orly Levkovitz; Sofia Bauer Rusek (MDPI AG, 2022)
Introduction: There is no agreement regarding the best method for tube-feeding preterm infants. Few studies, to date, have evaluated the influence of different methods of enteral feeding on intestinal oxygenation. The use of near-infrared spectroscopy (NIRS) has permitted the noninvasive measurement of splanchnic regional oxygenation (rSO2S) in different clinical conditions. The aim of this prospective, single-center study was to compare rSO2S during continuous versus bolus feeding among stable preterm infants. Methods: Twenty-one preterm infants, less than 32 weeks gestation and appropriate for gestational age, were enrolled. All infants were clinically stable and on full tube feedings. Each infant received a bolus feeding initially (20 min duration), and after 3 h, a continuous feeding (5 h duration). Infants were evaluated 30 min before and 30 min after the bolus and continuous feedings. The regional splanchnic saturation (rSO2S) was measured using near-infrared spectroscopy (NIRS) technology and systemic saturation was measured with pulse oximetry. From these measurements, we calculated the splanchnic fractional oxygen extraction ratio (FOES) for each of the four intervals. Results: rSO2S decreased after continuous vs. bolus feeding (p = 0.025), while there was a trend toward decreased SaO2 after bolus feeding (p = 0.055). The FOES, which reflects intestinal oxygen extraction, was not affected by the feeding mode (p = 0.129). Discussion/Conclusion: Continuous vs. bolus feeding decreases rSO2S but does not affect oxygen extraction by intestinal tissue; after bolus feeding there was a trend towards decreased systemic saturation.